2021
DOI: 10.3390/su132312978
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Perceptions of Agricultural Risks; Which Risk Attributes Matter Most for Men and Women

Abstract: Analysis of farmer risk perceptions is usually limited to production risks, with risk perception as a function of likelihood and severity. Such an approach is limited in the context of the many risks and other important risk attributes. Our analysis of the risk perceptions of farmers extends beyond production risks, severity of the risks, and their likelihoods. We first characterize agricultural risks and identify their main sources and consequences. We then analyze risk perceptions as a hierarchical construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Refs. [20][21][22][23][24]. These studies found several sociodemographic factors significantly affect farmers' risk perception and risk attitude.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Refs. [20][21][22][23][24]. These studies found several sociodemographic factors significantly affect farmers' risk perception and risk attitude.…”
Section: Introductionmentioning
confidence: 94%
“…Ref. [23] used the PLS-SEM approach to identify the impact of risk sources (namely low crop yields, fluctuating input prices, and reduction in agricultural incomes) on farmers' risk perception. He found that severity and ability to prevent a risk are most important in forming risk perceptions.…”
Section: Sem: the Path Analysismentioning
confidence: 99%